Eight free flaps in 24 hours: a training concept for postgraduate teaching of how to raise microvascular free flaps. Issue 1 (January 2016) - Bauer, Florian; Koerdt, Steffen; Hölzle, Frank; Mitchell, David A.; Wolff, Klaus-D.
Abstract: Microvascular free flaps are complex but important tools in oral and maxillofacial surgery (OMFS), and though techniques to raise flaps are challenging surgeons often have little structured training. In this study we have evaluated a structured, three-day, hands-on, practical training course on raising flaps. Five human, Thiel-embalmed cadavers were used for training in how to raise the following flaps: radial forearm, anterolateral thigh, lateral arm, fibular, latissimus dorsi, scapular, iliac crest, and rectus abdominis. The total duration of the course was 24 hours over three days. All participants were asked to evaluate the design and conduct of the course, their own learning curve, and general questions about their knowledge of how to raise flaps and microsurgery. There was a significant increase in participants' assessments of how they raised all free flaps, except the lateral arm flap (4.74 (0.68) compared with 2.42 (0.81); p=0.052) before and after the course. The radial forearm flap was thought to be the most relevant in clinical practice (n=40; 75%), followed by the anterolateral thigh (n=5; 9%) and fibular (n=4; 8%) flaps. Comparisons between residents and consultants showed unsurprising differences in experience with microsurgery and self-assessment in raising particular free flaps before the course. We have shown that a structured, hands-on course using a well-established simulation model can significantly improve postgraduate surgeons' skills in raising free flaps.